Safety quality of street-vended beef steak sold in two street vending sites in Metro Iloilo - Gabriel, Melissa Anne Tacorda (2004.)
There were five identified major street vending sites in Metro Iloilo.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Beef steak -- Street vended -- Safety quality; Metro Iloilo